Analysis of the breakthrough phenomena during heavy metal elution from a column packed with municipal waste incineration ash - Zhang, Wenqing; Yang, Yuesuo; Suganuma, Hideki; Kato, Shigeru; Suzuki, Seiichi; Kojima, Toshinori (Oficyna Wydawnicza Politechniki Wrocławskiej, 2018)
At some point during acid leaching column tests of heavy metals from municipal waste incineration ash, sudden and rapid elution of harmful elements was observed which was called the breakthrough (BT) phenomena. The mechanism was elucidated from the results of measurement of elemental and particle size distribution in the column and batch leaching tests as follows. At the first stage of experimental runs, CaCO3 was dissolved in acidic solution and pH profile along the bed is formed. Some of the minor elements of Zn and Al dissolved by acid at the upper part of the column are precipitated at bottom of the column, leading to the reduction of flow rate of the leachate solution. After leachate pH becomes low by the termination of dissolution of Ca, these deposits are dissolved and thus, the flow rate increases. Most of the trace elements behave as such, which causes the increase of harmful element concentrations in the eluate. Some drastic concentration increase of harmful elements in leachate may occur even after the long period of pseudo stable dissolution behavior in the land-fill site.
Environment Protection Engineering. Vol. 44, 2018, nr 3, s. 63-78
Keywords: ochrona środowiska; inżynieria środowiska; czasopisma